Implementasi Aplikasi Smart Farm Berbasis Android Menggunakan Metode Waterfall - Muzakki, Achmad; Amri, Arni Muarifah; Alhari, Muhammad Ilham; Sadam, Firlana (Jurnal Algoritma, 2025)
This study aims to develop an Android-based Smart Farm application. The main objective of this application is to improve operational efficiency and data recording accuracy. This application has livestock recording features, feeding schedules, and production report generation. With these features, it is expected that the application can help farm owners and officers in monitoring and managing farm activities efficiently and systematically. The methodology used in the development of this application is the Waterfall model, to provide more structured development and in accordance with the needs of farmers. Data for needs analysis were collected through field observations of farm owners and farm officers. The results show that this application facilitates monitoring of livestock conditions and feed management in real time. Based on these findings, this study recommends the addition of an automatic notification feature to improve farmers' responsiveness to farm needs.